History of Maternal Mortality in the City of Ribeirão Preto, in its Regional Health Department, and in the State of São Paulo after the Establishment of the Maternal Committees from 1998 to 2017 - Berezowski, Aderson Tadeu; Rodrigues Júnior, Antonio Luiz (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To describe the evolution of maternal mortality right after the establishment of maternal death committees in the region of the city of Ribeirão Preto, state of São Paulo, Brazil.Methods The present study describes the spatial and temporal distribution of maternal mortality frequencies and rates, using data from the state of São Paulo, the municipality of Ribeirão Preto, and its Regional Health Department (DRS-XIII) from 1998 to 2017. The present ecological study considered the maternal mortality and live birth frequencies made available by the Computer Science Department of the Brazilian Unified Health System (Departamento de Informática do Sistema Único de Saúde, DATASUS, in the Portuguese acronym)/Ministry of Health, which were grouped by year and political-administrative division (the state of São Paulo, the DRS-XIII, and the city of Ribeirão Preto). The maternal mortality rate (MMR) was calculated and presented through descriptive measures, graphs, and cartograms.Results The overall MMR observed for the city of Ribeirão Preto was of 39.1; for the DRS-XIII, it was of of 40.4; and for the state of São Paulo, it was of 43.8 for every 100 thousand live birhts. During this period, the MMR for the city of Ribeirão Preto ranged from 0% to 80% of the total maternal mortalities, and from 40.7% to 47.2% of live births in the DRS-XIII. The city of Ribeirao Preto had an MMR of 76.5 in 1998and 1999, which decreased progressively to 12.1 until the years of 2012 and 2013, and increased to 54.3 for every 100 thousand live births over the past 4 years. The state of São Paulo State had an MMR of 54.0 in 1998–1999, which varied throughout the study period, with values of 48.0 in 2008–2009, and 54.1 for every 100 thousand live births in 2016–2017. Several times before 2015, the city of Ribeirão Preto and the DRS-XIII reached the Millennium Goals. Recently, however, the MMR increased, which can be explained by the improvement in the surveillance of maternal mortality.Conclusion The present study describes a sharp decline in maternal death in the region of Ribeirão Preto by the end of 2012–2013, and a subsequent and distressing increase in recent years that needs to be fully faced.
Keywords: maternal mortality; health regionalization; mother and child healthcare